Value Co-creation and Customer Satisfaction in Business-to-Business Customer Relationships - Hopeaharju, Heta (My University, 2017)
Customer satisfaction is one of the key performance indicators in the case organization, and the company has recently launched a new concept to promote customer orientation and cooperation. This study aims to explain why some service units perform better and have better customer satisfactions than other units, and spot value co-creation practices that lead to better customer satisfaction. Thus, the purpose is to find out how value co-creation practices affect customer satisfaction in business-to-business relationships. Theoretical objective is to propose a framework combining value co-creation, customer satisfaction, and practices related to those concepts. Empirically, the objective is to acknowledge valuable practices creating customer satisfaction and collaboration and to offer managerial implications for the case organization. Concepts and models related to customer satisfaction and value co-creation are examined and discussed in the theoretical part of the study. Both concepts are presented by discussing theoretical frameworks, models, and aspects and practices identified in the existing literature and studies. From these premises, a conceptual interpretation is presented by combining both concepts and suggesting that value co-creation and practices related to it affect customer satisfaction. To study this relationship, the methodological study was conducted as case study and the data was mainly obtained by interviewing service managers of the chosen service units and representatives of their customers. Customer satisfaction and value co-creation seem to be interrelated concepts, and there are similar practices creating both customer satisfaction and enabling close collaboration with customers. Practices recognized from the interviews are also in line with previous literature and studies. In general, customer satisfaction is created by trust, communication, and collaboration which are also related to value co-creation. Managerially, it is suggested that company has established some practices well, while some practices, such as knowledge sharing and use of customer information, could be developed to improve customer satisfaction further. Managerial implications are presented at the end of the report.
Keywords: Value co-creation; Value coproduction; Customer satisfaction; Case study; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|